Prenatal Exposure to Phthalates and the Development of Eczema Phenotypes in Male Children: Results from the EDEN Mother–Child Cohort Study - Soomro, Munawar Hussain; Baiz, Nour; Philippat, Claire; Vernet, Celine; Siroux, Valerie; Nichole Maesano, Cara; Sanyal, Shreosi; Slama, Remy; Bornehag, Carl-Gustaf; Annesi-Maesano, Isabella (Environmental health perspectives, 2018)
Contradictory results exist regarding the importance of early-life exposure to phthalates for development of childhood eczema. We evaluated the association between maternal urinary concentrations of phthalate metabolites between the 24th and 28th week of gestation and occurrence of eczema in their sons up to 5 y of age, according to allergic sensitization as assessed by total immunoglobulin E (IgE) in a subsample of individuals. Data on health outcomes and background factors were collected using five standardized annual questionnaires completed by parents at the children's ages of 1-5 y, and their associations with phthalate metabolite urinary concentrations were assessed in 604 mother-son pairs with adjusted multiple logistic regression and Cox's survival model. Several eczema phenotypes were considered. Atopic status was assessed at 5 y of age in 293 boys through total IgE assessment. At 5 y of age, the prevalence of ever eczema was 30.4%. Metabolites of di-isobutyl phthalate (DiBP) and di-isononyl phthalate (DiNP) were positively associated with early-onset (0-24 mo of age) eczema (15.7%) and late-onset (24-60 mo of age) eczema (14.7%). Applying the Cox's model showed a significant association of occurrence of eczema in the first 5 y of life with DiBP and DiNP metabolites. Among IgE-sensitized boys, metabolites of di- -butyl phthalate (DBP) and DiBP were significantly associated with ever eczema {hazard ratio (HR)=1.67 [95% confidence interval (CI): 1.10, 2.54], =0.01 and HR=1.87 (95% CI: 1.01, 3.48), =0.04, respectively}. Occurrence of eczema in early childhood may be influenced by prenatal exposure to certain phthalates in boys. Further investigations are needed to confirm this observation. https://doi.org/10.1289/EHP1829.